Mechanical four-side rotary table position control device - WU YIFAN; WANG XICHUN; FAN CHENBIN; NIU ZHIQIANG; ZHOU LUN (2024)
The utility model relates to a mechanical four-side rotary table position control device which comprises an encoder, an encoder connecting flange is fixedly connected to a rotary shaft of the encoder, a connecting assembly used for being connected with a rotary table rotary shaft is connected to the encoder connecting flange, and the encoder is further provided with a fixing assembly used for fixing the encoder. The four-side rotary table has the effect of ensuring normal rotation of the four-side rotary table. 本申请涉及一种机械式四面转台位置控制装置，其包括编码器，所述编码器的转轴上固定连接有编码器连接法兰，所述编码器连接法兰上连接有用于连接转台转轴的连接组件，所述编码器上还设置有用于将所述编码器固定的固定组件。本申请具有确保四面转台的正常转动的效果。